Strategi Manajemen Hubungan Masyarakat Sebagai Branding MAN 1 Kota Malang - Fatimah, Siti (Proceedings Series of Educational Studies, 2024)
Abstract: The school-community relationship is a directed communication relationship between the school and the community that begins with knowing each other, understanding each other, helping and supporting each other. Public relations activities implemented in educational institutions use several techniques in the process by looking at the situation or condition of the surrounding environment. In this study the aim was to find out what techniques were used by MAN 1 Malang City in strengthening the relationship between the school and the community. The method used in this research is a qualitative method. Data collection techniques in this study were in the form of interviews, observation, and analysis of literature studies.Abstrak: Hubungan sekolah dengan masyarakat merupakan suatu hubungan antara sekolah dengan masyarakat yang berawal dari saling mengenal satu sama lain, saling memahami, saling menolong. Kegiatan humas yang diterapkan di lembaga pendidikan menggunakan beberapa teknik dalam prosesnya dengan melihat situasi atau kondisi dari lingkungan sekitar. Dalam penelitian ini bertujuan untuk mengetahui teknik-teknik yang dilakukan oleh MAN 1 Kota Malang dalam mempererat hubungan sekolah dengan masyarakat. Penelitian ini menggunakan metode kualitatif, yang mana dalam pengumpulan data berupa wawancara kepada salah satu pihak sekolah, observasi, dan analisis studi literatur.